Postmastectomy chest wall radiation of left-sided carcinoma breast - a dosimetric comparison between electrons and photons - Konakalla, V. L. Anusha; Darisi, Naga C. S.; Chandrasekharan, Kesavan; Naidu, D. S. Raju (International Journal of Research in Medical Sciences, 2022)
Background: For carcinoma breast patients requiring post mastectomy radiation therapy (PMRT), tangential photon beam (PB) is commonly used technique. The physical nature of electrons results in sharp dose fall off and reduces organs at risk (OAR) doses. Aim of the present study is to compare the coverage of chest wall and doses received by OARs – heart and lung between electron and photon beam plans in left sided breast cancer patients requiring PMRT. Methods: This study was done in 22 left sided carcinoma breast patients treated at GSL Medical College between May to December 2017. Both tangential PB plans and electron beam (EB) plans were generated on simulation computed tomography (CT) for each patient and both plans were compared. A dose of 50 Gy was prescribed to planning target volume (PTV) in 25 fractions. Results: The PB plans provided superior homogeneity index (HI) and conformity index CI compared to the EB plans (p<0.05). There was significant difference in favour of electron-beam plans for mean heart dose (p=0.0312), V25 Gy (p=0.029), V45 Gy (p=0.001) and V20 Gy of left lung (p=0.042). There was no significant difference in mean lung dose. Conclusions: Dosimetric data from this study suggests that PMRT with the electron beam can reduce doses to the heart and left lung with acceptable target coverage. It needs further research in the clinical setting.